2021-03-15 One-to-one Vs. Paired Interviews In Assessing Oral Proficiency. A Comparative Study Of A Group Of 3rd Year Efl Students At Constantine-1 University - Mohammed El Amine, SAIFI; Sarah, Merrouche (جامعة الوادي - University of Eloued, 2021)
Abstract The present paper provides a comparative framework of using individual (one-to-one) and paired interviews to assess EFL students’ oral proficiency at Constantine-1 University. Moreover, it investigates the students’ perceptions and attitudes towards undertaking each of the aforementioned assessments. Admittedly, the current study represents an individual renewal attempt to adapt and implement standardized oral tests in speaking classes. A sample of 3rd year EFL students were in a position to compare the common differences among individual and paired interviews in assessing oral proficiency through undertaking one particular testing method within each semester, and then answering a questionnaire. The results revealed better performances within paired interviews among the participants who admittedly enjoyed interacting with their peers rather than being alone in front of the teacher.
مقال
Keywords: paired interviews ; individual interviews ; oral proficiency ; the speaking skill ; interaction